Proposing a Workshop on Art Evaluation in University Teaching - Krzysztofik, Małgorzata; Zbróg, Piotr (Respectus Philologicus, 2020)
The article presents a workshop on art evaluation addressed at university students of the humanities. The aims of the workshop involve defining the terms ‘art’ and ‘kitsch’, analysing the functions of art throughout the ages, understanding the difference between an educated and uneducated art viewer, the importance of a canon of masterpieces of art for preserving the cultural heritage of Europe, and the problem of personal expectations concerning art. Scholarly content is presented to the students via a workshop based on coaching methods developed by cognitive psychology. The choice of this mode of work allows students to express themselves freely, teaches them how to defend their own opinions, improves their ability to see different points of view, and develops creativity. The workshop begins with a preliminary survey to identify the issues the students need help. It consists of 4 sessions (1.5 hours each) and ends with an evaluation. The proposed workshop can be extended with additional modules, tailored to the participants’ specific needs.
Keywords: academic teaching; art evaluation; kitsch; coaching methods